PENGARUH KELELAHAN EMOSIONAL TERHADAP PERILAKU MENYIMPANG KARYAWAN DENGAN VARIABEL MODERASI STRES KERJA - Sitawati, Ni Wayan Ari; Putra, Made Surya (E-Jurnal Manajemen, 2017)
The purpose of this study was to analyze the influence of emotional exhaustion against deviant behavior of employees and analyze the role of job stress in moderating influence emotional exhaustion against deviant behavior of employees. This research was conducted at the Hotel Bumi Ayu Sanur. The study used quantitative research methods, data collection using a questionnaire, as well as data analysis using the Moderate Regression Analysis (MRA). The number of samples in the study of 39 people. The results of data analysis showed that there is a positive influence on the emotional exhaustion of the deviant behavior of employees. This means that the higher the emotional exhaustion there will be a high deviation behavior in employees. Work stress acts as a moderating between emotional exhaustion with deviant behavior of employees. This means that any increase in the interaction of emotional exhaustion and job stress can decrease deviant behavior of employees.
Keywords: Kelelahan Emosional, Stres Kerja, Perilaku Menyimpang Karyawan